“Alternativas de diseño para solucionar los problemas presentados en las vías cahuají-el arrayán chico y Guso grande-Guso chico, perteneciente a la parroquia Guanando, cantón Guano, provincia de Chimborazo” - Rubén Abelardo, Aguilar Miranda (2016)
The following study, entitled "Design alternatives to solve the problems presented in the Cahuají-El Arrayán Chico and Guso Grande-Guso Chico roads, belonging to the Guanando Parish, Guano Canton, Chimborazo Province, has as main objective to open these Important accesses mentioned by what took into account the most important factors such as: agricultural and livestock production, commercial establishments located in the parish capital, the population working in the construction sector, plus the savings in time to achieve Communication with the closest cities and mainly the improvement of the quality of life of the inhabitants of the communities, since it is going to execute a study of ways that achieve the comfort and security at the moment of transit. The research for the project is mainly focused on a field study, because it is necessary to collect information in the sector where the new access routes will be implemented, first the geographical points of the land were obtained with their corresponding heights resulting in the topographic survey of Each of the strips for each route, and also recorded the current traffic of vehicles in each access establishing counting stations and also took soil samples from the subgrade to proceed in the laboratory to perform the respective tests, For later, to execute the work of cabinet where the study of traffic will be realized, horizontal and vertical design of the routes, design of the flexible pavement, design of works of drainage, calculation of volumes of work, budget and execution schedule.